Optimal sizing of hybrid Systems for Power loss Reduction and Voltage improvement using PSO algorithm: Case study of Guissia Rural Grid. (November 2022) - Djidimbélé, Répélé; Ngoussandou, Bello-Pierre; Kidmo, Dieudonné Kaoga; Kitmo,; Bajaj, Mohit; Raidandi, Danwe
Abstract: This work proposes a method for sizing and reducing power losses (MSRPL) of a hybrid photovoltaic and wind system (HPWS) in a radial distribution network (RDN) by developing an objective function, thanks to particles swarm optimization (PSO). The constraints defined on the objective function has permitted us to size the photovoltaic generator, wind turbine and total production cost. The proposed system configuration (PSC) improved the voltage level and minimized the power losses (PL) in the radial network. The proposed PSO algorithm was tested on Guissia (10°30'N, 15°18'E) rural electric grid (GREG) in the far north of Cameroon, which has a radial configuration. The integration of a battery bank allowed the system to have the power factor correction and production of active and reactive power. The test on IEEE 33-bus and IEEE 69 bus showed the robustness of the system and the reliability of the proposed method which also minimized the total cost of the system over 20 years.